Exploring the Different Roles and Aspects of Music - Pokharel, Ramesh (Molung Educational Frontier, 2020)
This paper explores different roles and aspects of music, describes its value, power and essential role in our daily life. The main objective of this article is to highlight the overall musical power in different aspects. Music affects both our body and mind. So, whenever we get time, we listen to Music. This makes us feel fresh even in old age. Music provides exercises to the mind. This is the reason why music is being used as therapy in hospitals even today. It has been seen that patients who listen to music take less time to improve. There are different genres of music like classical, semi-classical, light, folk, and their varieties of compositions with a magical quality, which we can enjoy according to our needs and requirements. Musical composition plays a vibrant part in everybody's normal life. It keeps us busy in free time. The rationalized sound, which arises from the creation of aesthetic-rasa, is called music. In eastern philosophy, Nada-Brahma (sacred-sound) is the primary source of music. This sound is called AUM, in which the whole universe remains vibrant. The impact of music on the living world is not hidden from anyone. Music is also the best way to practice yoga and meditation because it improves physical and mental health. It can be used for a therapeutic purpose too. It gives us peace in our challenging times and further enhances our happiness in good times. We can always use it to be happy. It is also beneficial for all professionals in different fields of society.